A retrospective study of miscarriages at Hospital USM from January 2011-December 2015 - Zulkefli, Aznoraini (2017)
Background: Miscarriage is a common early pregnancy complication. Until now there are still no local data regarding sociodemographic and clinical characteristics of miscarriages. This study addressed these issues by looking into five years of miscarriage cases at Hospital Universiti Sains Malaysia. Methodology: 230 cases that fulfil the criteria were selected randomly from all 736 cases of miscarriage treated at HUSM from the year 2011 – 2015, and all important data such as demography, reproductive profile, diagnosis or type of miscarriage, presenting symptoms, outcome were taken for analysis. Results: The proportion of miscarriage in the year 2011 – 2015 ranged between 1.01- 2.07%. The commonest type was incomplete miscarriage, followed by missed miscarriage, complete, threatened and inevitable miscarriage. Regardless of the type of miscarriage, vaginal bleeding was the most frequent presenting symptoms. Most of the cases were first-trimester miscarriages which frequently presented with incomplete miscarriage while second-trimester miscarriage presented mostly with missed miscarriage. There was no significant difference between first and second trimester miscarriages in term of age, BMI, marital status, occupational status, parity and history of miscarriage. Only 26 patients had complication related to miscarriage and most of them complicated with significant bleeding. Factors found to be associated with miscarriage in this study were age group 25-29-year-old, normal BMI, parity 1-3 and without any history of miscarriage. Conclusion: The proportion of miscarriage in HUSM was low. Further study in multiple centres may gain beneficial. Continuous education regarding preparation for optimum health condition before pregnancy must be promoted.